Manipulation and (mis)trust in prediction markets - Lawrence Choo; Todd R. Kaplan; Ro'i Zultan (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institute for Economics, 2019)
Markets are increasingly used as information aggregation mechanisms to predict future events. If policy makers make use markets, parties may attempt to manipulate the market in order to influence decisions. We experimentally find that policymakers could still benefit from following information contained in market prices. Nonetheless, manipulation is detrimental. First, manipulators affect market prices, making them less informative. Second, when there are manipulators, policy makers often ignore - or even act against - the information revealed in market prices. Finally, mere suspicion of manipulation erodes trust in the market, leading to the implementation of suboptimal policies - even without actual manipulation.
Keywords: C92; D53; D8; G14; 330; prediction markets; policy; experiment